KONFLIK ETNO RELIGIUS DI MYANMAR: KEKERASAN DAN PENGUASAAN MASAL TERHADAP KOMUNITAS ROHINGYA - Khofifah Sekar Ningrum (Adisam Publisher, 2024)
Ethnoreligious conflict in Myanmar, focusing on the violence and oppression experienced by the Rohingya community. The conflict involves multiple factors such as ethnic, religious, and political tensions that have led to a serious humanitarian crisis. This article explains the dynamics of the conflict, including the role of the Myanmar government, military, and extremist groups in curbing the rights and security of the Rohingya people. It also highlights the international response and human rights defence efforts in addressing the situation. Taking into account Myanmar's historical context and political dynamics, the research aims to understand the root causes of the conflict and seek sustainable solutions for peace and justice for the Rohingya community.